Analyzing the potential of cerbera odollam seeds and leaves as antibacterial agent - Nadiah Othman (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
The methanolic extractions from the parts seeds and leaves of Cerbera odollam were used in order to verify the antibacterial activity from different concentration of dilution prepared. Cerbera odollam leaves and seeds were collected nearby the School of Bipoprocess Engineering in Jejawi. The antimicrobial test was done to evaluate percentage of inhibition zone against e.coli and Bacillus cereus growth on media with different concentration of extracts dilution and different incubation time. The concentrations prepared were in 600 ppm, 800 ppm and 1000 ppm, while for incubation were from 48 hours, 72 hours and 96 hours. From screening process, seeds extraction was chosen. The optimizing condition was done for both bacteria by using Response Surface Methodology in Design of Expert. The results for experimental of optimum concentration and incubation time for Bacillus cereus was at 800 ppm, at 72 hours with 88% inhibition. Whereas, optimum concentration and incubation time for E. coli was at 800 ppm, at 72 hours with 78 %. From RSM analysis, the optimum process condition of seeds extract, on Bacillus cereus with concentration of 660 ppm, and incubation time at 88.80 hours. Then, on E.coli: with concentration at 760 ppm and incubation time at 78.80 hours.